Artery to Cystic Duct: A Consistent Branch of Cystic Artery Seen in Laparoscopic Cholecystectomy. (9th July 2015) - Rashid, Arshad; Mushtaque, Majid; Bali, Rajandeep Singh; Nazir, Saima; Khuroo, Suhail; Ishaq, Sheikh
Abstract : Uncontrolled arterial bleeding during laparoscopic cholecystectomy is a serious problem and may increase the risk of bile duct damage. Therefore, accurate identification of the anatomy of the cystic artery is very important. Cystic artery is notoriously known to have a highly variable branching pattern. We reviewed the anatomy of the cystic artery and its branch to cystic duct as seen through the video laparoscope. A single artery to cystic duct with the classical "H-configuration" was demonstrated in 161 (91.47%) patients. This branch may cause troublesome bleeding during laparoscopic dissection in the hepatobiliary triangle. Careful identification of artery to cystic duct is helpful in the proper dissection of Calot's triangle as it reduces the chances of hemorrhage and thus may also be helpful in prevention of extrahepatic biliary radical injuries.